PROSEDUR PEMERIKSAAN MRI PELVIS PADA KASUS KANKER SERVIKS DI INSTALASI RADIOLOGI RSUP PROF.DR.R.D.KANDOU MANADO - Angel, Angel Grace Meray; Astina, Kadek Yuna; Triningsih (LPPM Universitas Awal Bros, 2023)
Pelvic MRI examination procedure in case of cervic cancer in Radiology installation prof.Dr.R.D Kandou Manado is used as a reference for the author to conduct research with the aim of knowing the advantages and disadvantages of using 2 examination protocols .Cervical cancer is a disease characterized by uncontrolled cell growth and abnormal cell spread. Cervical cancer is the leading cause of cancer death for women in developing countries. Cervical cancer is the second most common cancer in the world from all cancers in women, this cancer reaches up to 15%. Currently, MRI is used as a way to diagnose cervical cancer. At the Radiology Installation of Prof.Dr.R.D.Kandou Hospital Manado, this examination uses a combination of 2 protocols, namely Abdomen-Pelvis MRI. This is a reference for the author to conduct research with the aim of knowing the advantages and disadvantages of using 2 examination protocols.This research is a qualitative research with a case study approach. In reviewing the problem, the author does not prove or reject the hypothesis made before the study but processes the data and analyzes the data non-numeric. This study used a sample of 5 cervical cancer patients and 3 research subjects for interviews. Results: Pelvis MRI examination procedure in cases of cervical cancer at Prof. RSUP. Dr. R. D. Kandou Manado includes patient preparation before MRI examination, equipment preparation, patient position, instrument position, examination protocol setting using 2 protocols, namely pelvic and abdominal MRI. The reason for using 2 protocols for pelvic MRI examination in cervical cancer cases at Prof. Hospital. Dr. R. D. Kandou Manado, the main thing is the doctor's request, in addition to the accuracy of the diagnosis, it can also detect the presence of metastases to organs other than the uterus. The advantages of using 2 pelvic MRI examination protocols in cervical cancer cases at Prof. Hospital. Dr. R. D. Kandou Manado, namely for the accuracy of diagnosing and knowing whether there are metastases in other organs, such as the liver, kidneys, lungs. While the lack of using 2 pelvic MRI examination protocols in cervical cancer cases, namely the examination time is longer than 1 examination protocol, but the difference is not too long. This examination does not use 2 examination protocols. However, specifically for examination with cervical cancer cases, 2 combinations are used as 1 examination protocol, namely the upper abdomen and pelvis. The purpose of using the